Style and Intersubjectivity in Youth Interaction - Djenar, Dwi (De Gruyter Mouton, 2017)
This book examines how style and intersubjective meanings emerge through language use. While numerous studies on youth language focus on face-to-face interaction, this book draws data from conversation, e-forums, teen fiction, and comics to offer an integrated account of language change in a community in flux.